2014
DOI: 10.1021/ja502030n
|View full text |Cite
|
Sign up to set email alerts
|

Transient Electrostatic Interactions Dominate the Conformational Equilibrium Sampled by Multidomain Splicing Factor U2AF65: A Combined NMR and SAXS Study

Abstract: Multidomain proteins containing intrinsically disordered linkers exhibit large-scale dynamic modes that play key roles in a multitude of molecular recognition and signaling processes. Here, we determine the conformational space sampled by the multidomain splicing factor U2AF65 using complementary nuclear magnetic resonance spectroscopy and small-angle scattering data. Available degrees of conformational freedom are initially stochastically sampled and experimental data then used to delineate the potential ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 75 publications
(130 reference statements)
5
90
0
Order By: Relevance
“…In particular, the conformations of the C-termini of GFP(À6) are the most distal ones with respect to the protein center and explain its slightly larger radius of gyration with respect to the two other constructs (Table 1). In conclusion, our results suggest that the conformational space of flexible parts is influenced by surface-charge distributions, a mechanism that has also been recently observed and quantified in flexible multidomain proteins and related to functionally important conformations (64).…”
Section: Discussionsupporting
confidence: 80%
“…In particular, the conformations of the C-termini of GFP(À6) are the most distal ones with respect to the protein center and explain its slightly larger radius of gyration with respect to the two other constructs (Table 1). In conclusion, our results suggest that the conformational space of flexible parts is influenced by surface-charge distributions, a mechanism that has also been recently observed and quantified in flexible multidomain proteins and related to functionally important conformations (64).…”
Section: Discussionsupporting
confidence: 80%
“…Consequently, no single preferred orientation of the two domains with respect to each other could be defined by the NMR and SAXS data. This is often observed for dynamic multidomain proteins, which sample a diverse continuum of conformations in solution involving encounter-like interdomain contacts (57)(58)(59). Unexpectedly, the amino acid residues in the C-terminal domain involved in interactions with the N-terminal domain are similar to those amino acids involved in nisin binding.…”
Section: Discussionmentioning
confidence: 91%
“…N-HSQC spectra of URRM1,2/U2AF35(UHM) (black), URRM1,2-M144I/U2AF35(UHM) (red), and URRM1,2-L187V/U2AF35 (UHM) (green). Discussion RNA binding of U2AF65 is associated with an open domain configuration, whereas unbound U2AF65 represents an ensemble of closed conformations (28,29). When analyzing its conformational dynamics, we found that U2AF65 can adopt different conformational states, dynamically switching between a closed conformation with a FRET efficiency of ∼0.96 and an open state with a FRET efficiency of ∼0.43.…”
Section: U2af35 Enhances Py-tract Recognition By a Dynamic Populationmentioning
confidence: 82%
“…Moreover, based on a combined analysis of NMR and small angle X-ray scattering (SAXS) data, it has been shown that the unbound RRM1,2 protein adopts a range of closed and detached domain arrangements, which are not able to mediate high-affinity RNA binding (29). To understand the…”
mentioning
confidence: 99%